Porous poly-l-lactide-co-ɛ-caprolactone scaffold: a novel biomaterial for vaginal tissue engineering. Issue 8 (15th August 2018) - Sartoneva, Reetta; Kuismanen, Kirsi; Juntunen, Miia; Karjalainen, Sanna; Hannula, Markus; Kyllönen, Laura; Hyttinen, Jari; Huhtala, Heini; Paakinaho, Kaarlo; Miettinen, Susanna
Abstract : The surgical reconstruction of functional neovagina is challenging and susceptible to complications. Therefore, developing tissue engineering-based treatment methods for vaginal defects is important. Our aim was to develop and test a novel supercritical carbon dioxide foamed poly-l -lactide-co-ɛ-caprolactone (scPLCL) scaffold for vaginal reconstruction. The scaffolds were manufactured and characterized for porosity (65 ± 4%), pore size (350 ± 150 µm) and elastic modulus (2.8 ± 0.4 MPa). Vaginal epithelial (EC) and stromal cells (SC) were isolated, expanded and characterized with flow cytometry. Finally, cells were cultured with scPLCL scaffolds in separate and/or co-cultures. Their attachment, viability, proliferation and phenotype were analysed. Both cell types strongly expressed cell surface markers CD44, CD73 and CD166. Strong expression of CD326 was detected with ECs and CD90 and CD105 with SCs. Both ECs and SCs attached and maintained viability on scPLCL. Further, scPLCL supported the proliferation of especially ECs, which also maintained epithelial phenotype (cytokeratin expression) during 14-day assessment period. Interestingly, ECs expressed uroplakin (UP) Ia, UPIb and UPIII markers; further, UPIa and UPIII expression was significantly higher on ECs cultured on scPLCL than on cell culture plastic. In conclusion, the scPLCL is potential scaffold for vaginal tissue engineering and the results of this study further illustrate the excellent biocompatibility of PLCL.